Relations between sexual satisfaction and satisfaction with the body image of obese women and women undergoing bariatric surgery (Research, Society and Development, 2021)
This article aimed to compare body image and sexual satisfaction in obese women and women undergoing bariatric surgery for at least 8 months; check the self-perception of both samples in relation to weight; to verify whether there is a correlation between satisfaction with body image and sexual satisfaction between the two groups. 258 women in an affective/sexual relationship participated, 100 of which were classified as having grade II obesity and 158 were in a condition after bariatric surgery. All participants answered the following instruments: Sociodemographic Characterization Questionnaire; Body Shape Questionnaire and the Sexual Satisfaction Scale for Women (SSS-W). For data analysis, descriptive statistical analysis, t test, ANOVA and Pearson correlation test were performed. As a result, it was found that the sexual satisfaction score in the SSSW was 106.57 (women undergoing surgery) and 102.98 (obese), with no significant difference (p > 0.05). In terms of body image satisfaction, among women with surgery, 47.46% were classified as satisfied, 25.95% as mildly dissatisfied, 18.36% as moderately dissatisfied and 8.23% as severely dissatisfied. Among obese women, 14% were satisfied, 15% were mildly dissatisfied, 43% were moderately dissatisfied and 28% were severely dissatisfied with their image. A statistically significant negative correlation (r = 0.40 p = 0.001) was found between Sexual Satisfaction and Body Image. It is concluded that, regardless of weight, there is a tendency that the greater the concern a woman has with her body image, the lower her sexual satisfaction will be.